An integrated approach based on micro-mapping analytical techniques for the detection of impurities in historical Zn-based white pigments. Issue 3 (19th February 2015) - Capogrosso, V.; Gabrieli, F.; Bellei, S.; Cartechini, L.; Cesaratto, A.; Trcera, N.; Rosi, F.; Valentini, G.; Comelli, D.; Nevin, A.
Abstract : We propose a combination of elemental and molecular μ-mapping techniques for the detection of trace metal ions and molecules in historical samples of Zn-based white pigments. Abstract : In this work we propose an integrated approach, based on synchrotron analysis with micrometric spatial resolution and sub-ppm sensitivity and μ-Raman mapping, for investigating impurities and heterogeneous inclusions in historical samples of Zn-based white pigments. Analysis was performed at the LUCIA beamline at the SOLEIL synchrotron radiation facility for the simultaneous detection of the elemental distribution in suitably prepared pigment samples using micro-X-ray fluorescence (μ-XRF) mapping and for the investigation of oxidation states and coordination of metals using micro-X-ray near edge absorption (μ-XANES) spectroscopy. The identification of specific molecular signatures and the detection of their spatial distribution throughout samples by μ-Raman measurements supported and complemented X-ray analysis, allowing the identification of Cr- and Fe-based inclusions in historical samples. In ZnO pigments, common impurities are due to the production process and include Fe and, depending on samples, Cd, Cl and Pb. In one of the Zn-containing pigments, identified as Lithopone, μ-XRF mapping revealed the presence of Co, both as highly concentrated micrometric inclusions and as impurities throughout the pigment.